UPAYA PENINGKATAN HASIL BELAJAR KETRAMPILAN LAY UP PADA BOLA BASKET MENGGUNAKAN PENDEKATAN PEMBELAJARAN PERMAINAN TRADISIONAL ENGKLEK PADA SMA N 4 SEMARANG (psnppg, 2025)
thus researchers will apply the Culturally Responsive Teaching (CRT) learning approach with the hopscotch game which is expected to improve the learning outcomes of lay-up skills in students at SMA N 4 Semarang. The purpose of this classroom action research is to improve the Learning Outcomes of Lay-Up Skills in Basketball Using the Traditional Hopscotch Game Learning Approach at SMA N 4 Semarang. Data collected in each activity from the implementation of the classroom action research cycle were analyzed descriptively using the N Gain test. the action using the culture responsive teaching learning approach with the traditional hopscotch game resulted in an increase with data of 0.4342 with the N gain criteria being in the middle so that further improvements are needed in the study. That by implementing the demonstration method using the culture responsive teaching approach using the traditional game of hopscotch, the activities and learning outcomes of students in physical education, sports and health learning in the material on basic lay up techniques in basketball in class XI 10 of SMA N 4 Semarang increased.
Keywords: Culturally Responsive Teaching; ketrampilan; Hasil Belajar